Dominican Republic : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2006)
The Dominican Republic has been working with the IMF to become a participant in the General Data Dissemination System, and already meets many of the recommendations and some of the encouraged categories for dissemination of macroeconomic statistics. The Dominican Republic has a statistical system that is centralized, mainly within the Central Bank of the Dominican Republic. Executive Directors suggest recommendations to increase further the Dominican Republic's adherence to internationally accepted statistical practices and enhance the analytical usefulness of the Dominican Republic's statistics.